Performance of the right ventricle under stress: relation to right coronary flow - Harold Brooks; Edward S. Kirk; Pantel S. Vokonas; Charles W. Urschel; Edmund H. Sonnenblick (The Journal of Clinical Investigation, 1971)
Right ventricular performance was studied relative to right coronary artery flow in the chloralose-anesthetized, open chest dog. The right coronary artery was cannulated for measurement and control of flow and pressure. Under control conditions, right coronary artery occlusion caused no change in cardiac output, or right and left ventricular pressures, although right ventricular contractile force fell markedly. With right coronary artery flow intact, incremental pulmonary artery obstruction caused a corresponding decline in cardiac output and elevation of right ventricular end-diastolic pressure with eventual total right ventricular failure and systemic shock. With right coronary artery occlusion, identical degrees of pulmonary artery obstruction resulted in more pronounced changes in cardiac output and right ventricular end-diastolic pressure with right ventricular failure occurring at a much lower level of right ventricular stress. However, with right coronary artery flow intact, the right ventricular decompensation induced by pulmonary artery obstruction, could be reversed by raising right coronary artery perfusion to levels above normal, thus increasing right ventricular performance and restoring cardiac output. We conclude that right ventricular failure and resultant systemic hypotension due to severe pulmonary artery obstruction can be reversed simply by right coronary artery hyperperfusion, and that, although a normally contractile right ventricular free wall is not essential to maintain cardiac performance at rest, during right ventricular systolic stress, over-all cardiac performance becomes increasingly dependent on the right ventricle. The data further imply that increased myocardial impingement on right coronary artery flow during systole in right ventricular hypertension may be an important factor leading to right ventricular failure. Images